(untitled) (Texas Journal of Medical Science, 2025)
This article provides a comprehensive analysis of the impact of long-term use of hypnotic drugs (benzodiazepines, Z-drugs, and melatonergic agonists) on cognitive functions. The neurobiological mechanisms of hypnotic agents—particularly changes in GABA-A receptor subunits, reduced synaptic plasticity in the hippocampus, and impaired memory consolidation—are outlined based on scientific literature. Research findings indicate that prolonged benzodiazepine use may reduce cognitive performance by 25–40%, while Z-drugs may decrease it by approximately 10–18%. Both reversible and irreversible forms of cognitive decline, along with their association with age, dosage, and treatment duration, are discussed. The study also examines the dynamics of cognitive recovery after discontinuation of hypnotics and evaluates the role of melatonin agonists, nootropics, and antioxidants in improving cognitive outcomes. The findings highlight the need for cautious and short-term use of hypnotic medications in clinical practice and form evidence-based recommendations for enhancing safety in the treatment of sleep disorders.